Keefektivan Konseling Rational Emotive Behaviour Untuk Menurunkan Kejenuhan Belajar Siswa SMP - Retnowati Retnowati (ILIN Institute, 2018)
This study aims to test the effectiveness of rational emotive behavior to reduce the saturation of junior high school students. This research uses pre experimental pre-test type post test one group design. The data analysis used is paired sample test T-test. at a significant level α = 0.05 (95%) then obtained t-table. = 1.812, assuming if t count> t-table then Ha "received" The results of data analysis of the respondents 'responses about students' learning saturation showed that the saturation of student learning before permberian counseling rational emotive behavior is in the category of being, and there is still a high category that is 11 respondents. As for after the treatment, based on the post test results indicate the criteria of saturation of learning students no one is in the high category. From the test results using T-Test proved that the counseling rational emotive behavior effective to reduce the saturation of students' learning junior high school.